Peran Serikat Pekerja Nasional (Spn) Di Dewan Pengupahan Dalam Pengawalan Penetapan Upah Minimum Kabupaten Dan Kota - Saepulloh, Asep; Laksana, April (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The phenomenon that occurs from year to year is that the determination of the Minimum Wage is always a hot topic of discussion between governments, employers and labor unions. Indonesian society is faced with the polemic of the suffocating price hike of oil and gasoline, which has resulted in scarcity that has caused changes in public behavior. Serang Regency as part of Banten Province also relies on industry. The issue of wages has always been a hot one and until now, the determination of minimum wages in the regions (regencies/cities) is the most obvious battlefield for workers/laborers. The determination of the City District Minimum Wage (UMK) is carried out by the Governor based on the Decent Living Needs (KHL) by taking into account economic growth and directed at achieving KHL in accordance with the components and stages of achieving KHL and taking into account the conditions of the business world's ability. The purpose of this research is to observe the role of the National Workers Union organization in overseeing wage determination. Trade unions have a role and function as a legal umbrella for workers who are active in industrial companies. The National Workers Union as a proponent in determining the minimum wage in the Wage Council. This research method uses a qualitative approach, while this type of research is juridical-empirical. Where researchers conducted direct research on the Minimum Wage negotiation process with stakeholders and elements of the Serang Regency Wage Board. The National Labor Union in this case has always been at the forefront of several unions that are members of the Alliance of Trade Unions (ASPSB). Any decision made by the Governor of Banten Province is followed by all unions and employers. Whatever the increase and percentage set by the government. Escorting the determination of the Minimum Wage cannot be separated from the role of the National Labor Union (SPN) in fighting for the rights sought for the welfare of workers.